PENGARUH EDUKASI GIZI DENGAN MEDIA MONTASE TERHADAP PENINGKATAN PENGETAHUAN TENTANG SAYUR DAN BUAH PADA SISWA SD IT PONDOK DUTA, KOTA DEPOK, TAHUN 2019 - Ulfa Yusa Handayani; Mohammad Furqan; Debby Endayani Safitri (Prosiding Seminar Nasional Berseri, 2020)
Consumption of vegetables and fruit for school children is very important to consume because it is needed by the body as a source of vitamins, minerals, and fiber to achieve optimal health. One of the factors that influence consumption of vegetables and fruits is knowledge. The purpose of this study was to determine the effect of nutrition education with montage media on increasing knowledge about vegetables and fruit in grade III elementary school students after getting an intervention using montage media. The design that used in this study was the Quasy Experiment Design with a purposive sampling method. The population in this study were students of class III (Three), amounting to 102 students at SD IT Pondok Duta, Cimanggis, Depok. The study was conducted on 100 students using a questionnaire before and after the intervention. Nutrition education media used is a montage entitled "Let’s Eat Vegetables and Fruits Every Day!". Data analysis used was univariate and bivariate analysis with Wilcoxon test. The results showed that there were significant differences between before and after Education with the Montage Media on the level of knowledge (<0,000), with a P value <0.05. Based on the results of this study it is suggested that there is an appropriate strategy and outreach to make montage media as an alternative to nutrition education media.